Should a Christian Adopt Methodological Naturalism? - Torrance, Andrew (Zygon, 2017)
It has become standard practice for scientists to avoid the possibility of references to God by adopting methodological naturalism (MN), a method that assumes that the reality of the universe, as it can be accessed by empirical enquiry, is to be explained solely with recourse to natural phenomena. In this essay, I critique the Christian practice of this method, arguing that a Christian's practices should always reflect her belief that the universe is created and sustained by the triune God. This leads me to contend that the Christian should adopt a theologically humble approach to the sciences (instead of MN), with which she humbly acknowledges that special divine action is not discernible by empirical science. To further my critique, I consider three ways in which the practice of MN can be particularly problematic for Christianity.